2019
DOI: 10.1002/acn3.715
|View full text |Cite
|
Sign up to set email alerts
|

A novel model for treatment of hypertrophic pachymeningitis

Abstract: Objective Immunoglobulin (Ig)G4‐related disease is a major cause of hypertrophic pachymeningitis (HP), presenting as a progressive thickening of the dura mater. HP lacks an animal model to determine its underlying mechanisms. We developed a suitable animal model for the treatment of HP. Methods We longitudinally evaluated dura in mice with a mutation (Y136F) in the linker for activation of T cells (LAT), which induced type 2 T helper (Th2) cell proliferation and IgG1 (IgG4 human equivalent) overexpression. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Overall, IgG4-related hypertrophic pachymeningitis is a rare disorder that has been diagnosed more frequently in Japan [ 12 , 14 ]. Differential diagnoses, in particular in cases with tumor-like intracranial manifestations, include lymphoma, sarcoidosis, and other immunological or infectious granulomatous diseases [ 3 , 20 ]. From a clinical point of view, the diagnosis should be based on radiological and laboratory findings as well as on the effectiveness of corticosteroid or immunosuppressive therapy [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, IgG4-related hypertrophic pachymeningitis is a rare disorder that has been diagnosed more frequently in Japan [ 12 , 14 ]. Differential diagnoses, in particular in cases with tumor-like intracranial manifestations, include lymphoma, sarcoidosis, and other immunological or infectious granulomatous diseases [ 3 , 20 ]. From a clinical point of view, the diagnosis should be based on radiological and laboratory findings as well as on the effectiveness of corticosteroid or immunosuppressive therapy [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It manifests as localized or diffused thickening of the dura mater [ 23 , 27 ]. Clinical manifestations depend on the location of the inflammatory lesion and on compression of neural structures leading to functional deficits [ 3 , 5 ]. A dural biopsy is commonly needed to establish a definite diagnosis [ 2 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several animal models of IgG4-RD have been established [ 19 22 ]. We first reported that LAT Y136F knock-in mice display several immunopathological features characteristic of IgG4-RD in organs such as salivary glands, pancreas, and kidney, as well as dural lesions in which many IgG1-positive cells and fibrosis are present [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The linker for activation of T cells (LAT) Y136F knockin mouse (LAT mouse) has been reported as a mouse with elevated type-2 T helper (Th2) cytokine and serum IgG1 (human IgG4-equivalent) levels [ 11 ]. In recent years, some reports showed that the LAT mouse could be an animal model of IgG4-RD [ 12 , 13 ]. LAT mice showed IgG1-positive plasmacyte infiltration and fibrosis in some organs, including the SGs, as well as elevated Th2 cytokine and serum IgG1 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%